10
$\begingroup$

Given an ellipse with foci $F_1, F_2$ and a point $P$. Let $T_1, T_2$ the points of tangency on the ellipse determined by the tangent lines through $P$. Show that $\widehat {T_1 P F_1} = \widehat {T_2 P F_2}$.

enter image description here

$\endgroup$
1
$\begingroup$

Let the ellipse be: $$\dfrac{x^2}{a^2}+\dfrac{y^2}{b^2}=1$$ Set $P(a,t)$, the tangent line $PT_1$ is $y=k(x-a)+t$, $k=\tan A_1$, since it is tangent line, so put in ellipse equation, we have: $$ b^2x^2+a^2(kx-ka+t)^2=a^2b^2$$ i.e., $$(b^2+a^2k^2)x^2+2a^2k(t-ka)x+a^2(t-ka)^2-a^2b^2=0$$ Solving for the point of tangency, the discriminant $\Delta$ must be zero: $$\Delta$=$4a^4k^2(t-ka)^2-4(b^2+a^2k^2)[a^2(t-ka)^2-a^2b^2] $$ At $\Delta=0$, we get $ 2kta-t^2+b^2=0$, that is, $k=\dfrac{t^2-b^2}{2ta}$.

Let $k_1$ be $PF_1$'s slope, $k_1=\dfrac{t}{a+c}=\tan A_2$, the $ \angle T_1PF_1=|A_1-A_2|$, now we calculate $\tan(A_1-A_2)$:

$$\tan(A_1-A_2)=\dfrac{\tan A_1-\tan A_2}{1+\tan A_1 \tan A_2}=\dfrac{k-k_1}{1+k k_1}=\dfrac{\dfrac{t^2-b^2}{2ta}-\dfrac{t}{a+c}}{1+\dfrac{t^2-b^2}{2ta}\dfrac{t}{a+c}}=\dfrac{(t^2-b^2)(a+c)-2at^2}{2at^2+2act+t^3-tb^2}$$

Since $b^2=a^2-c^2$, we get:

$$ RHS=\dfrac{(t^2-a^2+c^2)(a+c)-2at^2}{t(2a^2+2ac+t^2-a^2+c^2)}=\dfrac{c-a}{t}$$

Let $k_2$ be line $PF_2$'s slope, then $k_2=\dfrac{t}{a-c}=\tan\angle PF_2T_2$. Since $\angle T_2PF_2=\dfrac{\pi}{2}-\angle PF_2T_2$, so $\tan \angle T_2PF_2=\dfrac{1}{\tan\angle PF_2T_2}=\dfrac{a-c}{t}=\tan(A_2-A_1)$. Since the angles are acute, we have:

$\angle T_2PF_2=A_2-A_1=\angle T_1PF_1$

$\endgroup$
1
$\begingroup$

From Geometry Expressionsellipse angles

Equal by inspection.

$\endgroup$
1
$\begingroup$

Let $F_1'$ be the image of $F_1$ under reflection in the tangent at $T_1$. Since the tangent at $T_1$ is the external bisector of $\angle F_1T_1F_2$, the points $F_2T_1F_1'$ are collinear. Likewise, let $F_1''$ be the image of $F_1$ under reflection in the tangent at $T_2$; then $F_2T_2F_1''$ are collinear.

Diagram

Now,

  1. $F_1'P = F_1P = F_1''P$ by reflection,
  2. $F_2F_1' = F_2T_1+T_1F_1 = F_2T_2+T_2F_1 = F_2F_1''$ by reflection and the defining property of an ellipse,
  3. $F_2P = F_2P$.

By SSS, $\triangle F_2PF_1' \cong \triangle F_2PF_1''$. In particular, $$ \angle F_2PF_1' = \angle F_2PF_1'' = \tfrac12\angle F_1'PF_1'' \tag{1} $$

Next, by construction, reflecting in the tangent at $T_1$ and then in the tangent at $T_2$ sends $F_1'$ to $F_1$ and then to $F_1''$. But the composition of reflections in two lines is a rotation around their point of intersection, by twice the (directed) angle between the lines. Thus $F_1''$ is the image of $F_1'$ under a rotation around $P$ by $2\angle T_1PT_2$; in particular, $$ \angle F_1'PF_1'' = 2\angle T_1PT_2 \tag{2} $$

Combining (1) and (2) yields $$ \angle T_1PT_2 = \angle F_1'PF_2 $$ Subtracting $\angle T_1PF_2$ from both sides yields $$ \angle F_2PT_2 = \angle F_1'PT_1 $$ Finally, by reflection, $\angle F_1'PT_1 = \angle F_1PT_1$, so $$ \angle F_2PT_2 = \angle F_1PT_1 $$ as desired.


Incidentally, from $\triangle F_2PF_1' \cong \triangle F_2PF_1''$ it also follows that, letting $Q$ be the intersection of $F_2T_1$ and $F_1T_2$, the triangle $F_1T_1Q$ and $F_2T_2Q$ have a common excircle, whose centre is $P$.

$\endgroup$
0
$\begingroup$

HINT: It is enough to prove that enter image description here Where n is normal unit vector. NOTE: parametric equation is γ(t)= (p cos t, q sin t)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.